2009
DOI: 10.1080/08995600902768800
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Automation for Human Supervision of Multiple Uninhabited Vehicles: Effects on Change Detection, Situation Awareness, and Mental Workload

Abstract: Human operators supervising multiple uninhabited air and ground vehicles (UAVs and UGVs) under high task load must be supported appropriately in context by automation. Two experiments examined the efficacy of such adaptive automation in a simulated high workload reconnaissance mission involving four subtasks: (a) UAV target identification; (b) UGV route planning; (c) communications, with embedded verbal situation awareness probes; and (d) change detection. The results of the first "baseline" experiment establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(89 citation statements)
references
References 31 publications
4
83
1
1
Order By: Relevance
“…In addition, limited automation was invoked that paired vehicles and targets, subject to operator override. This builds on a similar study performed by Parasuraman, Cosenzo, and De Visser (2009) by testing attentional aiding in addition to automation.…”
Section: Introductionmentioning
confidence: 86%
“…In addition, limited automation was invoked that paired vehicles and targets, subject to operator override. This builds on a similar study performed by Parasuraman, Cosenzo, and De Visser (2009) by testing attentional aiding in addition to automation.…”
Section: Introductionmentioning
confidence: 86%
“…Their results showed that the participant's performance with adaptive automation was better compared to fully manual operation, but that adaptive automation also was more effective when supporting less cognitively demanding stages of information processing (e.g., information acquisition and action implementation) than more cognitively demanding stages (e.g., information analysis and decision making). Parasuraman et al (2009) investigated the effect of an adaptive automation system for a human operator supervising multiple unmanned vehicles. The adaptive automation was adjusted based on the human operator's performance in a change detection task.…”
Section: Low High Routine Performancementioning
confidence: 99%
“…Though some studies have successfully employed adaptive automation using a specific triggering condition (e.g., Parasuraman et al, 2009), there has not been a great deal of research on the relative merits of the various triggering conditions for adaptive automation (Kaber, 2012;), yet their importance to human-automation collaboration is widely acknowledged (Kaber, 2012;Sheridan & Parasuraman, 2005). Since there are relative benefits and disadvantages to each type of techniques mentioned in Section 2.2.7, several authors have recommended the use of hybrid methods to ensure that automation is initiated (or changed) when it should be (Parasuraman et al, 1996;Sheridan & Parasuraman, 2005).…”
Section: Low High Routine Performancementioning
confidence: 99%
See 2 more Smart Citations